esource Mobilisation in Entrepreneurial Ventures (1987 - 2019): An Integrative Review and Opportunities for Future Research - Adegbile, Abiodun S.; Theo Wagner, Heinz-Theo; Söllner, Albrecht (Senate Hall, 2020)
This paper provides an integrative picture of the state of the art of the Resource Mobilisation in Entrepreneurial Ventures (RMEV) literature through a systematic review of 225 peer-reviewed journal articles published between 1987 and 2019. Our objective is to synthesise the relevant resource mobilisation-centred work into a framework that contributes to and shapes our understanding of the RMEV phenomenon. We construct the identified themes through a process of interpretation and representation in which the information we study remains contextualised. Based on the themes we identify, we suggest some directions for further research. Moreover, by simultaneously considering the opportunity exploitation and resource-constrained environment assumptions in a coherent framework, we provide a conceptual bridge between these two RMEV assumptions. The constructed framework facilitates a better understanding of the emergence and performance of entrepreneurial ventures.
Keywords: strategic entrpreneurship|review|entrepreneurial ventures